A dynamic load distribution algorithm for virtual worlds - Farooq, U.; Glauert, J. (Journal of Digital Information Management, 2010)
The introduction of modern communication and computation technologies has greatly changed the traditional approaches processing computationally intensive applications such as Virtual Environments (VEs). Distributed and multi-server architectures are scalable and exploit the concepts of spatial and temporal locality for handling massive Distributed VEs (DVEs). However, using these environments require special attention for scalability, consistency, load balancing, and latency. The existing mechanisms primarily developed for games have key performance issues in managing large scale virtual worlds. In our previous work (Farooq and Glauert, 2009a), we have proposed a hierarchical infrastructure named JoHNUM for the development of scalable and consistent virtual worlds. Further, we have introduced the concept of aggregate region assignment to minimise resource utilisation and distribute the load as balanced as possible among servers (Farooq and Glauert, 2009a, 2009b). This paper presents our proposed load distribution algorithm that yields regular and contiguous areas for assignment. It examines possible combinations of regions based on proposed strategies but greatly reduces the aggregation process by using different filters. It also presents a simple communication model justifying the proposed strategies and load distribution algorithm. Simulation results with an extended set of experiments show that the proposed algorithm obtains fair distribution of load and has the capability to cope with small, medium and large scale environments while minimising communication and implementation cost.
Keywords: Consistency; Load balancing; Scalability; Second life; Virtual Environment; Virtual world